2004
DOI: 10.1249/01.mss.0000147629.74832.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance, Endurance, and Concurrent Exercise on Training Outcomes in Men

Abstract: Concurrent training performed by young, healthy men does not interfere with strength development, but may hinder development of maximal aerobic capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
92
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 24 publications
15
92
1
9
Order By: Relevance
“…Compared to the single exercise, whole body RT increased the total amount of skeletal muscle mass (e.g., increase in fat-free mass), which is thought to be related, in part, to changes in VO 2 max [17]. However, despite the increases in fat-free mass or muscle fiber size, these studies still observed no significant increase in VO 2 max [7,15,20]. Furthermore, it is reported that there was no significant change in mitochondria enzyme activity (e.g., citrate synthase and succinate dehydrogenase) following RT [7,37].…”
Section: Effects Of Training Volumementioning
confidence: 79%
See 2 more Smart Citations
“…Compared to the single exercise, whole body RT increased the total amount of skeletal muscle mass (e.g., increase in fat-free mass), which is thought to be related, in part, to changes in VO 2 max [17]. However, despite the increases in fat-free mass or muscle fiber size, these studies still observed no significant increase in VO 2 max [7,15,20]. Furthermore, it is reported that there was no significant change in mitochondria enzyme activity (e.g., citrate synthase and succinate dehydrogenase) following RT [7,37].…”
Section: Effects Of Training Volumementioning
confidence: 79%
“…Previous RT studies reported that fat-free mass (FFM) increased~2 kg following 8-12 weeks of training [15,20,21]. It is presumed that approximately half of the increased FFM is skeletal muscle mass [2].…”
Section: Changes In Muscle Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Foram consideradas não treinadas as voluntárias que não participavam de um programa de treinamento físico pelo menos três meses antes, além de não estarem envolvidas em nenhum tipo de exercícios regulares durante a realização do estudo (19) . As voluntárias foram subdivididas em dois grupos:…”
Section: Métodos Sujeitosunclassified
“…Esse aumento em resposta ao treinamento de resistência de força não é um resultado consensual, não sendo observado em alguns estudos (12,13,19,24) , enquanto outros relataram aumento nesse índice (14,16) . Além disso, outra diferença do presente estudo se deve à participação exclusiva de mulheres, podendo sugerir o comportamento de determinado gênero em resposta ao treinamento; as voluntárias realizaram os testes cardiopulmonares antes e após 12 semanas, independente da fase do ciclo menstrual, pois, embora o controle dessa variável seja uma preocupação notória em estudos com mulheres, pesquisas anteriores demonstraram que a fase do ciclo menstrual não altera a capacidade cardiorrespiratória em mulheres (25,26) .…”
Section: Tabela 3 Variáveis Cardiopulmonares Dos Grupos Experimentalunclassified